The Diachronic Change of the Practice of Iftā’: From Individual to Collective - Yakar, Emine Enise (Islamic Studies, 2021)
The connection between Islamic legal methodologies and practice in the development of Islamic law has been made by the practice of iftā’. Governmental and non-governmental religious institutions, along with individual Muslim scholars, emerged as the sources of legal authority. Although the origin of the practice of iftā’ can be traced back to the time of the Prophet Muḥammad (peace be on him), its nature has changed from individual to collective in the modern age. The contemporary Muslim world has witnessed a rapid proliferation of modern religious institutions of fatwās, which significantly contributed to the dynamism of Islamic law and the regulation of local and regional practices. The practice of iftā’ can be described as a legal formulation produced during the consultation process between a lay Muslim and a Muslim scholar. The product of iftā’ is known as fatwā, which is an Islamic legal opinion that Muslim scholars issue to clarify a legal problem that Muslims face. Since the twentieth century, the practice of iftā’ has begun to be assumed by modern religious institutions. This institutionalization process resulted in the practice of collective iftā’. Contrary to scholars who allege the immutability of Islamic legal methodologies, this change can be interpreted as demonstrating the progressive dimension of Islamic law within the area of legal theories and methodologies. The paper seeks to examine the diachronic transformation of fatwā and explores the driving factors behind the instrumentalization of collective fatwā. After giving a detailed terminological definition of fatwā, the research introduces the differences between fatwā (Islamic legal opinion) and ḥukm (court verdict) to forestall any terminological complexity. The diachronic process is then addressed by referring to key turning points that evidence the transformation of the practice of iftā’ from individual to collective. In the last instance, public, state, and collective fatwās are engaged to adduce the diversification within the end-products of the practice of iftā’.